(untitled) (Journal of Enam Medical College, 2015)
Background: Guttate psoriasis has a well-known association with streptococcal throat infections, but the effects of these infections in patients with chronic plaque type of psoriasis remains to be evaluated. In Bangladesh several studies were done on psoriasis but no data about association between streptococcal throat infection and plaque type psoriasis are available so far. Considering the co-morbidities of psoriasis patients, it might be justifiable to find out the events that provoke the initiation or exacerbation of psoriatic disease process. Objective: To observe the association of streptococcus with plaque type of psoriasis. Materials and Methods: This observational study was conducted in the department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University, Dhaka. Forty seven patients clinically and histopathologically diagnosed as having plaque psoriasis were selected as cases and patients with skin diseases other than psoriasis were selected as controls. Results: In this study majority of subjects (55%) were diagnosed as chronic plaque psoriasis. Among the subjects with guttate flare of chronic plaque psoriasis 64.2% gave a positive history of sore throat. ASO titer was raised (>200 IU/mL) in 28 (59.5%) patients of chronic plaque psoriasis and 7 (17.9%) patients of non-psoriatic respondents. The difference between two groups was significant (p<0.05). Streptococcus pyogenes was found in 12 (25.5%) in chronic plaque psoriasis patients versus in 4 (10.2%) in controls (p>0.05). Conclusion: This study shows that streptococcal throat infections are associated with plaque psoriasis and early treatment of throat infections may be beneficial for plaque type of psoriasis patients. J Enam Med Col 2015; 5(2): 99-103